Effect of food intake on 92 biomarkers for cardiovascular disease - Dencker, Magnus (Lund University, 2017)
Objective: The present study evaluates the effect of food intake on 92 biomarkers for cardiovascular disease (CVD).
Methods: Twenty two healthy subjects (11 male and 11 female aged 25.9±4.2 years) were investigated. A total of 92 biomarkers were measured before a standardized meal as well as 30 and 120 minutes afterwards with the Proseek Multiplex CVD III kit.
Results: The levels for eight biomarkers decreased significantly (P<0.05) 30 minutes after food intake. The levels for seven biomarkers remained significantly decreased 120 minutes after food intake. Nine biomarker decreased significantly at 120 minutes after food intake. The changes were between 4-30%, most commonly around 5%. Only six biomarkers showed a difference of 10% or more due to food intake. The biggest differences were observed for Insulin-like growth factor-binding protein 1 (30%); Azurocidin, Cystatin-B, and Myeloperoxidase (13%); Monocyte chemotactic protein 1 (11%); and Myeloblastin (10%), all 120 minutes after food intake.
Conclusions: This study shows that food intake affects several different CVD biomarkers, but the effect is predominantly modest. Timing of blood sampling in relation to food intake, therefore, appears not to be a major concern. Further studies are warranted in older healthy subjects and in patients with various cardiac diseases to determine whether the findings are reproducible.
Purpose:
The present study evaluates the effect of food intake on 92 biomarkers for cardiovascular disease with the Proseek Multiplex CVD III kit.

Studien studerade effekten av matintag på 92 kardiovaskulära biomarkörer (Proseek Multiplex CVD III, Olink), på 22 friska personer före, 30 och 120 minuter efter mat intag. Total sänktes nivån för 8 biomarkörer signifikant av matintag 30 minuter, 7 biomarkörer var fortfarande sänkta 120 minuter efter matintag. Förändringarna var ofta <10%, bara 6 biomarkörer hade mer än 10% förändring. Störst förändring hittades för; Insulin-like growth factor-binding protein 1 (30%); Azurocidin, Cystatin-B, och Myeloperoxidase (13%); Monocyte chemotactic protein 1 (11%); och Myeloblastin (10%), alla 120 minuter efter matintag.
Syfte:
Att studera effekten av matintag på 92 kardiovaskulära biomarkörer.
Effekt av matintag på 92 kardiovaskulära biomarkörer
Keywords: cardiovascular disease; kardiovaskulär sjukdom; biomarkers; biomarkörer; food intake; matintag; HEALTH; HÄLSA; Medical and Health Sciences; Medicin och hälsovetenskap